HIBAH BAGIAN HARTA BERSAMA SUAMI KEPADA SAUDARA ISTRI DITINJAU MENURUT HUKUM ISLAM (Studi Kasus di Pengadilan Agama Kelas II Palopo) - Syarif Husain Ahmad (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2018)
The judge's view of the existence of a grant made by an heir to you without the knowledge of other heirs is deemed invalid because the grant must be carried out with the knowledge of the heirs, moreover the donation is still in the status of a joint asset, then the property that is donated cannot be withdrawn back as stipulated in article 212 Compilation of Islamic Law.